PENGARUH PENEMPATAN DAN PENGALAMAN TERHADAP KEPUASAN DAN KINERJA KARYAWAN - Wijaya, I Made Bagus Githa; Suana, I Wayan (E-Jurnal Manajemen, 2013)
This study aims to determine how much influence the placement and experience the satisfaction and performance of employees. Respondents in this study focused on food and beverage service employees, amounting to 43 people at Hotel Melia Benoa. Anaylisis lane or path analysis is used as a data analysis technique in this study. Results of the study show the placement and experience a positive and significant impact on satisfaction and employee performance and job satisfaction and a significant positive effect on employee performance. Keywords: Employee Performance, Satisfaction, placement, experience